Dismantling the dream factory : gender, German cinema, and the postwar quest for a new film language - Baer, Hester (New York : Berghahn Books, 2009)
The history of postwar German cinema has most often been told as a story of failure, a failure paradoxically epitomized by the remarkable popularity of film throughout the late 1940s and 1950s. Through the analysis of 10 representative films, Hester Baer reassesses this period, looking in particular at how the attempt to "dismantle the dream factory" of Nazi entertainment cinema resulted in a new cinematic language which developed as a result of the changing audience demographic. In an era when female viewers comprised 70 percent of cinema audiences a "women's cinema" emerged, which sought to.
Relegitimating cinema: female spectators and the problem of representation -- How do you solve a problem like Susanne?: the female gaze in Wolfgang Staudte's The murderers are among us (1946) -- When fantasy meets reality: authorship and stardom in Rudolf Jugert's Film without a title (1948) -- Gendered visions of the German past: Wolfgang Liebeneiner's Love '47 (1949) as woman's film -- Unsolved mysteries: race, ethnicity, and gender in Helmut Kätner's Epilogue (1950) -- Art on film: representing gender and sexuality in popular cinema -- "Through her eyes": regendering representation in Willi Forst's The sinner (1951) -- Looking at Heimat: visual pleasure and cinematic realism in Alfons Stummer's The forester of the silver wood (1955) -- Degenerate art?: problems of gender and sexuality in Veit Harlan's Different from you and me (175) (1957) -- Towards the new wave: gender and the critique of popular cinema -- Pleasurable negotiations: spectatorship and genre in Helmut Kätner's "anti-tearjerker" Engagement in Zurich (1957) -- Sound and spectacle in the Wirtschaftswunder: the critical strategies of Rolf Thiele's The girl Rosemarie (1958) -- Gender and the new wave: Herbert Vesely's The bread of those early years (1962) as transitional film -- Epilogue: adapting the 1950s: the afterlife of postwar cinema in post-unification popular culture.
Includes bibliographical references (pages 283-289) and index.
Print version.
JSTOR
Keywords: Motion pictures -- Germany -- History -- 20th century; Motion pictures -- Social aspects -- Germany -- History -- 20th century; Motion pictures for women -- Germany -- History -- 20th century; Motion picture audiences -- Germany -- History -- 20th century; Women in motion pictures -- History -- 20th century; Cinéma -- Allemagne -- Histoire -- 20e siècle.; Cinéma -- Aspect social -- Allemagne -- Histoire -- 20e siècle.; Films de femme -- Allemagne -- Histoire -- 20e siècle.; Cinéma -- Publics -- Allemagne -- Histoire -- 20e siècle.; Femmes au cinéma -- Histoire -- 20e siècle.; ART -- Film & Video; PERFORMING ARTS -- Film & Video -- Reference; PERFORMING ARTS -- Film & Video -- History & Criticism; Motion picture audiences; Motion pictures; Motion pictures for women; Motion pictures -- Social aspects; Women in motion pictures; Germany; Film history, theory & criticism; Gender studies, gender groups; Germany; Performing Arts; 1900-1999; History